P199 Outcomes of Crohn's rectovaginal fistulae in a specialist centre. (15th January 2020) - Twum-Barima, C; Iqbal, N; Reza, L; Vaizey, C; Hart, A; Tozer, P
Abstract: Background: Rectovaginal fistula (RVF) is a devastating complication of Crohn's disease (CD). Despite advances in medical and surgical treatment, management of CD RVF remains challenging. Surgery is the principal treatment with adjunctive medical therapy. This study tracks patients from initial fistula presentation through their treatment pathways. Methods: We reviewed our retrospective RVF database (2009–2019). Patients were captured through imaging and surgical coding. Outcomes included patient satisfaction, fistula closure and stoma reversal. Results: We identified 66 patients with CD RVF from our database of 327 RVF patients, with a median age of 40 years and mean follow up of 6.3 years. Cross-sectional analysis of patients' initial symptoms, management and outcomes identified three groups: 1-quiescent luminal disease, with minimal fistula symptoms; 2-quiescent luminal disease, but moderate fistula symptoms (suitable for RVF repair); 3-poorly controlled luminal disease and active fistula, requiring medical control and/or defunctioning before RVF repair. Thirty-one patients were identified in group 1 ('minimal symptoms'). The median age was 37 years and most were on Infliximab (32%) or combination therapy (45%). Patients reported a negative impact on the quality of life (QoL) (39%), such as sex avoidance and psychosocial impairment. Some patients later required defunctioning (22%) or proctectomy (13%). Fistula symptoms improved in 16% following medical treatment alone. One patient developed a mucinous adenocarcinoma. Nine patients were identified in group 2 ('immediately suitable for repair'). The median age was 44 years. A low QoL was reported in 44%. Reparative procedures included rectal advancement flap and omentoplasty. Two patients were defunctioned. Fistula closure was seen in 44% after medical and surgical treatment. Twenty-six patients presented in group 3 ('poorly controlled luminal disease and active fistula') and 17 patients joined this group after symptom deterioration (15 from group 1 and 2 from group 2). The median age was 45 years. All patients were on biologics/combination therapy and defunctioned. Some 30% underwent proctectomy. Some patients declined stoma reversal (7%) and proctectomy (12%). Markedly poor QoL was reported in 35% of patients. Medical escalation resulted in fistula closure in 14% of patients. Conclusion: Complex RVF with poorly controlled disease requires faecal diversion/proctectomy and optimal medical therapy. Well-timed reparative surgery in a selected group yields reasonable outcomes. Management is dependent on factors such as the extent of CD, fistula symptoms, response to medical treatment, suitability for local repair and patient choice.